Comparison of Vitamin D Levels in Patients with Chronic Lymphocytic Thyroiditis and the Normal Population, and Role of Vitamin D on Autoimmunity - Serkan Yıldırım (Genel Tıp Dergisi)
Purpose It is known that vitamin D deficiency has a role in the formation of autoimmune diseases, inflammatory bowel disease, rheumatoid arthritis, multiple sclerosis, diabetes, many types of cancer and heart diseases. This study was conducted to demonstrate the role of vitamin D in Hashimoto's thyroiditis. Methods In this cross-sectional study, the patients who applied to Izmir Bozyaka Training and Research Hospital endocrinology outpatient clinic between the ages of 16 and 50 were evaluated with ultrasonographically consistent with chronic thyroiditis, serologically antibody positive (anti T, anti M), euthyroid, body mass index (BMI) <30, 40 women with Hashimoto's thyroiditis who did not enter menopause, did not have any other additional disease and did not use chronic medication, and 16-50 women who applied to the internal medicine or endocrinology polyclinics of Izmir Bozyaka Training and Research Hospital 40 healthy female patients with a body mass index (BMI) <30 years and negative for thyroid antibodies were recruited. Results When the two groups were compared in terms of age, body mass index, t3, t4, TSH, Anti M, Anti T and vitamin D, no statistically significant difference was found between the two groups. As a result of the Spearman correlation test, no statistically positive or negative correlation was found between vitamin D level and any other parameter (p >0.05). Conclusion In conclusion, in this study, it was seen that there may be a relationship between Hashimoto's thyroiditis and vitamin D deficiency. Since vitamin D levels were found to be deficient in the control group, a clear interpretation cannot be made regarding the correlation of Hashimoto's thyroiditis and vitamin D deficiency based on the findings of this study. We hope that our study will be helpful for further studies that will investigate the relationship between autoimmune thyroid diseases and vitamin D deficiency.